2016
DOI: 10.3382/ps/pew243
|View full text |Cite
|
Sign up to set email alerts
|

Spatial influence on breast muscle morphological structure, myofiber size, and gene expression associated with the wooden breast myopathy in broilers

Abstract: The wooden breast (WB) myopathy is identified by the palpation of a rigid pectoralis major (p. major) muscle and is characterized as a fibrotic, necrotic p. major disorder in broilers. The objective of the current study was to determine spatial morphological and gene expression differences at 4 locations within WB affected muscle from different genetic lines. Morphology was evaluated in 2 broiler lines expressing the WB myopathy (Lines A and B) and a line without WB (Line C) at 3 ventral locations and one ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 80 publications
6
84
1
Order By: Relevance
“…They also reported that only breast WS/WB presented lower DPA and EPA contents. Changes in the chemical composition of WB and WS/WB meats are consistent with the replacement of fibers by adipose tissue (lipidosis) and the accretion of extracellular water as a result of edema and inflammatory processes (Clark & Velleman, ; Kawasaki, Iwasaki, Yamada, Yoshida, & Watanabe, ).…”
Section: Physicochemical and Histological Properties Of Wb Ws And Smmentioning
confidence: 67%
See 2 more Smart Citations
“…They also reported that only breast WS/WB presented lower DPA and EPA contents. Changes in the chemical composition of WB and WS/WB meats are consistent with the replacement of fibers by adipose tissue (lipidosis) and the accretion of extracellular water as a result of edema and inflammatory processes (Clark & Velleman, ; Kawasaki, Iwasaki, Yamada, Yoshida, & Watanabe, ).…”
Section: Physicochemical and Histological Properties Of Wb Ws And Smmentioning
confidence: 67%
“…This condition might even be exacerbated by the physiology of the pectoralis major muscle: its impressive development (with particular reference to thickness) might compress the pectoral artery thus further reducing oxygenation and nutrients transportation to the muscle. This hypothesis is further supported by the evidence that the severity of the histological lesions, associated with the occurrence of WS, WB, and SM, gradually decreases moving from the skin-facing surface towards the inner section of the pectoralis major (Baldi et al, 2018;Clark & Velleman, 2016;Soglia et al, 2016a). In addition, hypoxic conditions seem to be exacerbated by the reduced blood vessel density observed in WB affected muscles (Sihvo et al, 2018) as well as by tissue swelling likely due to the accumulation of compounds having osmotic properties (that is, taurine and alanine) (Boerboom et al, 2018).…”
Section: Underlying Causes Of Wb Ws and Smmentioning
confidence: 84%
See 1 more Smart Citation
“…With the knowledge that WBD presents itself bilaterally, in this study, the upper 1/3 or craniolateral aspect of right superficial pectoral muscle was used consistently as the sampling site on all samples. The choice for this specific location was guided by the knowledge that clinical, gross and histological changes associated with WBD are largely known to start from the cranial aspect of the muscle before becoming apparent caudally (Clark & Velleman, 2016). Further, muscle samples excised from this site were about 2-3 cm deep from the outer aspect of the muscle.…”
Section: Necropsy Protocolmentioning
confidence: 99%
“…The breast muscle was palpated to examine birds for hardness, before euthanasia. This approach has been used as a diagnostic method in several recently published studies [10,26,27]. Birds were then euthanized by cervical dislocation and dissected for the collection of tissues for genetic analysis.…”
Section: Sample Collection and Rna Extractionmentioning
confidence: 99%